2009
DOI: 10.1111/j.1464-410x.2008.08284.x
|View full text |Cite
|
Sign up to set email alerts
|

Laser treatment of benign prostatic hyperplasia in patients on oral anticoagulant therapy: a review

Abstract: We assessed the therapeutic efficacy and safety of laser prostatectomy (LP) for treating benign prostatic hyperplasia (BPH) in patients on oral anticoagulation. We systematically reviewed previous reports, using the Pubmed database and bibliographies of retrieved articles and reviews. The oral anticoagulation included coumarin derivatives and platelet‐aggregation inhibitors (PAI). Previous studies do not allow the establishment of definitive conclusions for managing patients on oral anticoagulation and who req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 22 publications
1
20
0
2
Order By: Relevance
“…GreenLight PVP laser showed positive results in several studies in the short and medium term in patients with LUTS secondary to BPO [2,3,4,5,10,11,12,13,15,20], including a better safety profile than monopolar TURP in patients on antiplatelet or anticoagulant treatment [6,7,8,21]. Very few published data tell us about the long-term outcome of PVP [1,4,11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GreenLight PVP laser showed positive results in several studies in the short and medium term in patients with LUTS secondary to BPO [2,3,4,5,10,11,12,13,15,20], including a better safety profile than monopolar TURP in patients on antiplatelet or anticoagulant treatment [6,7,8,21]. Very few published data tell us about the long-term outcome of PVP [1,4,11,12].…”
Section: Discussionmentioning
confidence: 99%
“…This technique is particularly useful in aging patients or patients with antiplatelet or anticoagulant treatment since it appears to better control the bleeding risk [6,7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews have confirmed that photoselective vaporization of the prostate also has excellent hemostatic properties in these patients and the 2 modalities are probably equivalent in smaller prostates (up to 60 g). However, in larger prostates HOLEP is probably superior in safety, efficacy and time efficiency [14,23]. …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that HOLEP is at least as effective at improving obstructive symptoms with shorter hospitalization and catheter time and importantly less blood loss [10,11,12,13,14]. Two recent studies have supported the safety of HOLEP in anticoagulated patients [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Holmium laser enucleation of prostate). On vrši vrlo dobru hemostazu zbog čega njime možemo sa sigurnošću liječiti pacijente koji su na antikoagulantnoj terapiji 22 . Laser valne duljine 532 nm, čiji je predstavnik KTP laser GreenLight TM , koji emitira kvazikontinuirani val, gotovo u potpunosti se apsorbira od strane hemoglobina, što rezultira fotoselektivnom vaporizacijom prostate PVP (engl.…”
Section: Laserske Tehnikeunclassified